ANALISIS KEKUATAN VELG ALUMUNIUM MODEL D30D PADA PERUSAHAAN “A” - Sumiyanto, Sumiyanto; Abdunnaser, Abdunnaser (Bina Teknika, 2018)
Wheels are one of the main components in a vehicle. Without wheels of vehicles will not be to function. The damage that occurs in aluminium alloy wheels for the outbreak spoke mostly occur due to a force and tension that occurs exceeds the maximum allowable voltage. With these considerations it is necessary to redesign using 3D software and simulated using finite element method. After simulated, part produce with low pressure casting and machining. Sample part test with several testing as single part such as : life test, drum test, 13° impact test. After that sample part test as running test such as : curb stone evaluation and rectangle evaluation. The results of sample testing parts such as life test, the drum test, 13 ° impact test and running test in the form of curb stone rectangle evaluation and evaluation did not reveal any cracks on the sample part. Nut torque results of sample testing parts such as curb stone evaluation have smaller in 70 N.m, with allowed limit 61,6 N.m until 88 N.m. And nut torque results of sample testing parts such as rectangle evaluation have smaller in 76 N.m, with allowed limit 61,6 N.m until 88 N.m